Study on the Modification Formula of Earth Material Compound with Cement and Gravel by Single Lattice Theory - Kun Zhang; Bai-Ru Lu; Yi-Hong Wang; Zhan Qu; Le Qu (Advances in Civil Engineering)
Gravel and cement can effectively improve the low strength of traditional Earth materials. There have been few studies on test methods for raw soil-based composite admixtures. By introducing the theory of single lattice formula testing, the compressive strength of 10 formulas and 60 modified raw soil cubic specimens were tested. The failure process, failure mode, and compressive strength of specimens were studied. The effects of different formulations of raw soil on strength, peak displacement, and dispersion were analyzed. The results showed that cement content had a significant effect on the compressive strength and dispersion of earth material specimens. The optimal modification formula of cement, gravel, and raw soil was determined to be 0.1/0.08/0.82 (mass ratio). At the same time, the applicability of the test method was verified, which can be used as a reference for the experimental study on modification formulations of earth materials.